'n Perspektief op makrogemeentes vanuit die wesensaard van die kerk volgens die Nuwe Testament - HC van Zyl (Acta Theologica)
The article argues the case for New Testament guidelines to the phenomenon of macro congregations today - churches in excess of 3 500 church members. After dealing with some methodological matters, the following topics are created: the church being both an eschatological community - a foreign body in che world - and part of this world. Sub-topics like the church as small group and large community, unity and diversity, and charism and office in the church, are created. The article concludes with a view remarks from the above exposition with a view co macro congregations.